Confessional State and Human Rights in Costa Rica - Alpízar Jiménez, Idalia (2018)
This paper develops a historical approach to the topic of the confessional State in Costa Rica within a human rights framework. It analyzes both the context from the moment in which the conquest and colonization started, and the role played by the evangelizers to the side of the Spanish colonizers. The article analyzes the role the Catholic Church played in the process of formation of the national State and the benefits the Church obtained as a result. It evaluates the implications in the area of human rights that have been exercised in the Costa Rican society. This evaluation had recourse to bills of law submitted by the Movement for a Secular State in Costa Rica; these bills seek to remove the article 75 and to amend the article 175 of the Constitution.